Do Seasonal Tropical Storm Forecasts Affect Crack Spread Prices?. Issue 5 (16th February 2013) - Fink, Jason; Fink, Kristin
Abstract Individual storms in the Gulf of Mexico have been shown to affect crack spread futures prices. As hurricanes strike refiner‐dense areas, prices of refined petroleum products rise. We find that crack spread prices are even affected by seasonal hurricane forecasts. We find this despite the difficulties of long horizon forecasting, and that refiners are only exposed in a small portion of the Atlantic basin. These effects are economically important. For example, a one standard deviation increase in the June forecast of the net tropical cyclone activity in the upcoming season increases 3‐2‐1 crack spread prices by over 9%. © 2013 Wiley Periodicals, Inc. Jrl Fut Mark 34:420–433, 2014